Implementasi Teknologi Tepat Guna Daur Ulang Sampah Plastik sebagai Paving Block Ramah Lingkungan - Dwi Nor Halisa; Laili Hidayah; Rendy Damar Sutanto; Muhammad Anzwar Daenuri; Kholifah Umi Sholihah (Muria Jurnal Layanan Masyarakat, 2025)
This community service program aims to raise environmental awareness and empower the community of Karangampel Village in managing plastic waste through education, training, and mentoring in producing paving blocks made from recycled plastic waste. The activities were carried out through socialization, technical training, and direct mentoring for community members and the Karang Taruna youth organization. The results showed an increased public understanding of plastic waste management, the formation of new habits in waste segregation, and the emergence of local initiatives in developing recycled products. In addition, the active involvement of Karang Taruna served as an important indicator of social transformation through local leadership roles. This program is expected to become a model for sustainable community empowerment in the fields of environmental management and the creative economy.Â Pengabdian masyarakat ini bertujuan untuk meningkatkan kesadaran lingkungan dan memberdayakan masyarakat Desa Karangampel dalam mengelola sampah plastik melalui edukasi, pelatihan, dan pendampingan pembuatan paving block berbahan daur ulang sampah plastik. Kegiatan ini dilaksanakan dengan metode sosialisasi, pelatihan teknis, serta pendampingan langsung kepada masyarakat dan Karang Taruna. Hasil program menunjukkan adanya peningkatan pemahaman masyarakat tentang pengelolaan sampah plastik, terbentuknya kebiasaan baru dalam pemilahan sampah, serta munculnya inisiatif lokal dalam mengembangkan produk daur ulang. Selain itu, keterlibatan aktif Karang Taruna menjadi indikator penting munculnya transformasi sosial melalui peran kepemimpinan lokal. Program ini diharapkan mampu menjadi model pemberdayaan masyarakat yang berkelanjutan di bidang lingkungan dan ekonomi kreatif.